Development of targeted nanocapsules using pomegranate peel extract with enhanced bioavailability and anti-inflammatory activity for ulcerative colitis: In vitro studies - P. Monika; M.N. Chandraprabha; R. Hari Krishna; Vittal Maanya; C. Likhitha; N. Pooja (Hybrid Advances)
The study aimed to establish an accurate drug delivery system with a tailored mechanism for the efficient management of Ulcerative Colitis (UC). Using the solvent evaporation technique, nanoencapsulation of pomegranate peel extract (PPE) in biodegradable enteric polymer methacrylic acid-ethyl acrylate copolymer (Eudragit L-100) was prepared. In vitro drug release investigations indicated a greater percentage of drug released at 6.8 pH in contrast to 7.4 pH (96.98 ± 0.80 % vs. 93.97 ± 0.711 %), indicating its applicability in the region of the human intestine. The mechanism of drug release from the nanoformulations (NFR) exhibited a process controlled by Fickian diffusion. The results suggest efficient encapsulation of PPE within Eudragit L100 and may be used for targeted drug release in the intestinal region. Anti-inflammatory studies on the HIEC-6 cell line showed that tumour necrosis factor-α (TNF-α) expression was significantly (p < 0.001) decreased in all NFRs. Additionally, NFRs exhibited antioxidant activity and enhanced in vitro bioavailability (in intestinal pH compared to gastric pH).